THE STUDY OF THE COMPOSITION OF THE EXTRACT AND ANTIMYCOTIC PROPERTIES ANTHEMIS ALTISSIMA L. - Mustafayeva, Sitara Jalal; Serkerov, Sirajeddin Veli; Bakhshaliyeva, Konul Farrux (Химия растительного сырья, 2019)
The qualitative and quantitative composition of chemical components of ethanol extract of the above-ground part of Anthemis altissima L. (syn. Cota altissima (L.) J.Gay) species (family Asteraceae) collected during flowering phase from the flora of Azerbaijan has been studied. The chemical composition of ethanol extract was analyzed by chromatography-mass-spectrometry methods. 54 components were identified in the extract. As a result of the study, it was found that the A. altissima contained benzene aromatic compounds (77.21%). Among them Benzene, (1-butylheptyl) – 7.84%, Benzene, (1-propyloctyl) – 7.71%, Benzene, (1-pentyloctyl) – 7.03%, Benzene, (1-pentylheptyl) – 5.69%, Benzene, (1-butyloctyl) – 5.37%, Benzene, (1-propylnonyl) – 5.02% were the main components. In addition to the above components in the extract of the aerial part other biological active substances, such as alcohols (6.37% – of them prevail Hop-22(29)-en-3. β.-ol – 1.53%, γ-Sitosterol – 1.32%), esters of acids (5.3% – of them prevail Hexadecanoic acid, ethyl ester – 0.88%; Linoleic acid, ethyl ester – 0.63%) and alkanes (1.64% – of them prevail Eicosane – 0.53%; Pentacosane – 0.40%) were also identified. The share of unidentified components was 8.99%. The article also presents the results of the study of the antifungal properties of A. altissima and its aqueous extract against the culture of pathogenic fungi Fusarium oxysporium and Aspergillus niger. The aqueous extract of A. altissima, in contrast to the plant itself, shows a fungistatic effect on the fungi Fusarium oxysporum and Aspergillus niger.